2011
DOI: 10.1037/a0024491
|View full text |Cite
|
Sign up to set email alerts
|

The functional unit of Japanese word naming: Evidence from masked priming.

Abstract: Theories of language production generally describe the segment as the basic unit in phonological encoding (e.g., Dell, 1988; Levelt, Roelofs, & Meyer, 1999). However, there is also evidence that such a unit might be language specific. Chen, Chen, and Dell (2002), for instance, found no effect of single segments when using a preparation paradigm. To shed more light on the functional unit of phonological encoding in Japanese, a language often described as being mora based, we report the results of 4 experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
113
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(127 citation statements)
references
References 29 publications
12
113
2
Order By: Relevance
“…In addition, these findings were also consistent with the data based on speech errors (see O'Séaghdha, 2015, for review) and the studies using the masked primed naming paradigm (e.g., Verdonschot, et al, 2011;You, Zhang, & Verdonschot, 2012). However, some recent studies suggest that the preparation unit is not immutable even within the same language.…”
Section: The Flexibility Of Preparation Unitssupporting
confidence: 80%
“…In addition, these findings were also consistent with the data based on speech errors (see O'Séaghdha, 2015, for review) and the studies using the masked primed naming paradigm (e.g., Verdonschot, et al, 2011;You, Zhang, & Verdonschot, 2012). However, some recent studies suggest that the preparation unit is not immutable even within the same language.…”
Section: The Flexibility Of Preparation Unitssupporting
confidence: 80%
“…The same paradigms that provide evidence for Table 2 Examples of the pictures used in Experiment 2 (from the homogeneous set /t/) this view in Dutch and English do not support it in Chinese and Japanese (for results from implicit priming, see Chen et al, 2002;Kureta et al, 2006; for results from masked priming, see Chen et al, 2003;Verdonschot et al, 2011). To retain the generality of the model while accommodating the cross-linguistic variations, O'Seaghdha et al (2010) proposed the language-general proximate units principle, according to which word-form encoding starts with the first selectable phonological unit below the word level.…”
Section: Discussionmentioning
confidence: 99%
“…The idea that orthography might have something to do with the kind of production effect observed in a language was tested recently by Verdonschot et al (2011) in Japanese using the masked-priming paradigm. The authors observed priming effects for the mora but not for the segment, no matter whether kana (a mora-based script) or romaji (Romanized Japanese, a segment-based script) were used, which indicates that the language-specific production effect is not motivated by language-specific orthography.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the two syllable Japanese word Nissan (日産; the Japanese automaker) can be separated into four morae as ni.s.sa.n. These units play an important role in Japanese phonology and in fact are considered the basis of its speech rhythm (Kubozono, 1985(Kubozono, , 1989Kureta, Fushimi, & Tatsumi, 2006;Otake, Hatano, Cutler, & Mehler, 1993;Port, Dalby, & O'Dell, 1987;Warner & Arai, 2001). Verdonschot et al (2011) interpret this mora-level MOPE in Japanese in terms of the speech planning model and conclude that the mora is the functional phonological unit of speech planning in this language.…”
mentioning
confidence: 96%